The Role of KM Tactical Factors in Supply Chain Management for Gaining Competitive Advantage - Behzadi, Sara; Koochakzadeh, Rooghayeh Sadat (ExcelingTech, 2019)
Supply chain management (SCM) has assumed a leading operations strategy position in both manufacturing and service industries, and over the past 10 years companies have seriously implemented supply chain management strategies in their organizations. knowledge management(KM) is a major enabler of supply chain management, and is a critical element in information intensive and multi-cultured enterprise environments. The present study aimed to investigate the role of KM tactical factors in gaining competitive advantage in organizations. For this purpose, four tactical factors of KM (knowledge acquisition, knowledge sharing, learning from KM process, and knowledge application) and five indicators of gaining competitive advantage (timely supply of products) were studied and the relationships between them were analyzed.The statistical findings confirmed the effect of KMtactical factors on gaining competitive advantage. In addition, the results indicated that KM process should be scientifically implemented by using experts to gain competitive advantage. Creating the necessary infrastructures and appropriate acculturalization seem essential.